Indigenous knowledge source: Plants and animals as traditional medicine dayak tamambaloh’s of labian ira'ang village - Adriana Gandasari; Markus Iyus Supiandi; Didin Syafruddin; Serafin Tanti Nita; Mawardi Mawardi; Siti Zubaidah; Susriyati Mahanal (STKIP Persada Khatulistiwa Sintang, 2023)
Indigenous knowledge regarding plant and animal knowledge as traditional medicine in the Tamambaloh Dayak community in Labian Ira'ang Village has been passed down from generation to generation. The aim of the researchers is to explore the ethnography of the sources of animal and plant knowledge as traditional medicine in the Tamambaloh Dayak community, Labian Ira'ang Village. Data processing was carried out qualitatively using data mapping and data reduction techniques. The results of data processing are presented in the form of data presentations by displaying comprehensive data and the results of the research are presented in a qualitative descriptive manner. The study involved two traditional healers or medicinal shaman as subject I and eight people with disease who were purposively selected to be subject II divided into two categories, namely external disease and internal disease. The results of the research show that the source of knowledge about plants and animals as traditional medicine is obtained through ancestral revelations given in dreams as evidenced by the presence of supernatural shamanic insights from elders and obtained from the family tree.